EVALUATION OF THE BITCOIN MINING PROJECT FOR 5-YEARS PERIOD USING REAL OPTIONS WITH LEARNING PROCESS - Andika Dani Fajar Suryawa, Febi
Bitcoin is one type of cryptocurrency that is very potential to be used as investment because it has volatile price fluctuations with high volatility. In this final project, the real options method that we used as a strategy analysis method to model the decision making to maximize the investment made in the bitcoin mining project for 5-years period. Bitcoin is a high risk asset so learning about the project before making an investment will have an impact on the return of the project. The real options method with learning process feature is used as a strategy analysis for running bitcoin mining project. The method that we used for the valuation of project and real options are binomial method with time varying and trinomial method with volatility changing. Strategy analysis is needed to model the decision making in the future in order to maximize the return of investment on the project.